Knowledge and Attitudes of Heath Care Providers towards induced abortion in the City of Kigali - Jean Paul Ndayizeye; Connie Mureithi; Monica Mochama; Erigene Rutayisire (Journal of Public Health International, 2022)
This study investigated the healthcare provider’s knowledge and attitudes towards induced abortion in Rwanda. A total of 152 healthcare providers from six public hospitals in Kigali city participated in this study. Questionnaires were used to record data on demographics, level of knowledge and attitudes towards abortion law then be cleaned, coded and entered into Excel sheet. Then all data were exported into SPSS version 22 for final cleaning and analysis. The study findings revealed that 54.6% were female, 56.0% were single, and 73% participants said that they attended formal training on abortion care. The study findings revealed that 23.70% healthcare providers had poor knowledge towards legal abortion law, and 57.20% had positive attitude with regards to induced abortion law. The findings revealed that religion and formal training on abortion care were among the factors which were strongly influencing attitudes of health care providers towards induced abortion where protestants were unlikely to have positive attitude with regards to induced abortion (AOR=0.277; 95% CI=0.027-0.377; P=<0.001) compared to participants belonged to catholic religion and participants who were not trained were unlikely to have positive attitude with regards to induced abortion (AOR=0.696; 95% CI=0.056-0.721; P=0.048) compared to trained respondents. It concludes that marital status, category of caregiver, religion, formal training on abortion and level of knowledge were the main risk factors of level of attitude towards induced abortion. More training about induced abortion are highly needed among health care providers to increase related knowledge as well as to eliminate negative attitude towards induced abortion.
Keywords: Abortion law